Molecular surveillance and antimicrobial susceptibility profile of bacterial contamination in pastries of Iranian confectioneries: a public health concern - Hosseini, Shiva; Motallebirad, Tahereh; Mohammadi, Mohammad Reza; Safarabadi, Mehdi; Beheshti, Zeynab; Orouji, Mohammad Ali; Mardanshah, Omid; Azadi, Davood (Frontiers in Microbiology, 2024)
IntroductionMicrobial contamination in food products such as pastries, poses a significant public health concern due to the potential risks of foodborne infection and outbreak, Therefore, to prevent these infections, it is essential to investigate the frequency and extent of microbial contamination as well as the level of drug resistance in pastries. Due to this issue, our study aimed to assess the microbial diversity and the drug susceptibility patterns of microbial pollutants in pastry shops in Markazi province, Iran.MethodsThe study involved collecting 120 pastry samples from 30 pastry shops in Markazi province, Iran. The isolates were identified using a series of biochemical, phenotypic, and molecular assays, including specific PCR and 16S rRNA gene sequencing. Drug susceptibility testing (AST) was performed by using the Kirby-Bauer method according to the CLSI 2023 guidelines.Results and discussionA total of 56 isolates (46.66%) were recovered from 120 pastries samples, The most prevalent species isolated in the current study were S. aureus 12 isolates (21.43%), M. luteus 7 isolates (12.5%), E. coli 7 isolates (12.5%), S. warneri 6 isolates (11.12%), 6 isolates of S. succinus (11.12%), B. cereus 5 isolates (10.7%), Nocardia 4 isolates (7.15%), K. pneumoniae 3 isolates (5.35%), S. epidermidis 3 isolates (5.35%), and E. faecium 3 isolates (5.35%). The isolates showed the most sensitivity to imipenem and trimethoprim-sulfamethoxazole and the least sensitivity to erythromycin and tetracycline. The AST showed that 7 isolates of S. aureus were MRSA, 3 isolates of E. coli and, 2 isolates of K. pneumoniae were identified as ESBL. In conclusion, the results of the current study showed that the microbial contamination of pastries produced in confectionaries of Markazi province was not in standard ranges. These problems may be related to fecal contamination of pastries or lack of hygiene by handlers and it is urgent to develop the standards of hygiene of food handling techniques and aseptic pastry production in confectioneries.